2018
DOI: 10.9734/jalsi/2018/45113
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Total Phenolic and Flavonoid Contents of Petroselinum crispum Mill.

Abstract: Background: Petroselinum crispum is a common vegetable or spice in Egypt and worldwide. It possess many pharmacological and medicinal properties. Aims: In the current research, the total phenolic and flavonoid contents as well as the antioxidant activities of P. crispum methanolic extract and its fractions were evaluated. Methodology: The total phenolic content was estimated by Folin-Ciocalteu method and total flavonoid content was tested by aluminum chloride assay. The antioxidant activity was evaluated by 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
2
16
2
Order By: Relevance
“…Moreover, in the same study, it was suggested that apiin and apigenin exhibit strong protection against lipid peroxidation as determined via the TBARS assay, although no synergistic effects were observed for the joint incubation of these compounds [28]. Although phenolic compound content was associated with antioxidant activity in several studies [5,30,42,45], our results did not confirm this trend, probably due to different assays being performed and the presence of other compounds not determined in this study. Different capital Latin letters in the same column indicate significant differences between the means of the three types of cultivars according to Tukey's honestly significant difference (HSD) test at p = 0.05, while different small Latin letters in the same column indicate significant differences between the means of the cultivars of the same type according to Tukey's HSD test at p = 0.05.…”
Section: Antioxidant Activitycontrasting
confidence: 62%
See 2 more Smart Citations
“…Moreover, in the same study, it was suggested that apiin and apigenin exhibit strong protection against lipid peroxidation as determined via the TBARS assay, although no synergistic effects were observed for the joint incubation of these compounds [28]. Although phenolic compound content was associated with antioxidant activity in several studies [5,30,42,45], our results did not confirm this trend, probably due to different assays being performed and the presence of other compounds not determined in this study. Different capital Latin letters in the same column indicate significant differences between the means of the three types of cultivars according to Tukey's honestly significant difference (HSD) test at p = 0.05, while different small Latin letters in the same column indicate significant differences between the means of the cultivars of the same type according to Tukey's HSD test at p = 0.05.…”
Section: Antioxidant Activitycontrasting
confidence: 62%
“…Besides its widespread use as a fresh legume and garnishment, P. crispum is proposed for diverse therapeutic determinations in daily medicine for antioxidant, hepatoprotective, anti-diabetic, antibacterial, antifungal, analgesic, diuretic, hypotensive, gastroprotective, immunosuppressant and other effects [3], which are attributed to a broad variety of active compounds detected in this plant. Parsley plant parts (the leaf, stem and root) are rich sources of bioactive compounds such as furanocoumarins (e.g., xanthoxin, trioxalen and angelicin), essentials oils (e.g., sesquiterpene hydrocarbons, monoterpene hydrocarbons and alcohols, furanocoumarins, aldehydes and aromatic compounds), flavonoids (e.g., quercetin, apiol, myristicin, apigenin, luteolin and their glycosides), carotenoids (e.g., neoxanthin, β-carotene, lutein and violaxanthin), vitamins (e.g., tocopherols and A, C and B complexes), minerals (e.g., iron, zinc, calcium and phosphorous) and fatty acids (e.g., linolenic and palmitic acid) [1,[3][4][5][6][7][8][9]. Notably, numerous bioactive properties have been attributed to the leaves of P. crispum, which are reported for the handling of immune diseases, inflammation, anaemia, hyperlipidaemia and diabetes and in the relief of the symptoms of allergies, chronic bronchitis, dyspepsia, hypotension, thrombosis and strokes, among other diseases [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has documented the biological activity (antioxidant, hepatoprotective, antimicrobial) of several classes of phytochemicals that can be found in different parts of parsley, such as flavonoids, coumarins or lipids [31][32][33][34][35]. However, to our knowledge, this is the first study to investigate the change in parsley metabolome induced by treatments with biocontrol agents.…”
Section: Discussionmentioning
confidence: 92%
“…The aluminum chloride colorimetric procedure was applied to quantify the total flavonoid content (TFC) of each extract, as illustrated by Fattahi and his team, 23 with slight modification. An aliquot of 50 µL of each extract (2.5 mg/mL) was mixed with 300 µL of 5% (w/v) sodium nitrite (Ajax Finechem, New Zealand) and 300 µL of 10% (w/v) aluminum trichloride (Ajax Finechem, New Zealand), followed by the addition of 4 mL of distilled water.…”
Section: Total Flavonoid Content (Tfc)mentioning
confidence: 99%